Doom guy : life in first person - Romero, John, 1967- (Abrams Press, 2023)
"John Romero, gaming's original rock star, is the cocreator of DOOM, Quake, and Wolfenstein 3-D, some of the biggest video games of all time. Considered the godfather of the first-person shooter, a genre that continues to dominate the market today, he holds a unique place in gaming history. In DOOM Guy: Life in First Person, Romero chronicles, for the first time, his difficult childhood and storied career, beginning with his early days submitting Apple II game code to computer magazines and sneaking computers out the back door of his day job to write code at night. Industry-redefining breakthroughs in design and tech during Romero's time at id Software made DOOM and Quake cultural phenomena, and this thrilling story recounts every step of the process, from collaborative, heavy metal-fueled days spent crafting the industry's most revolutionary and cutting-edge games to a high-profile falling-out with id cofounder John Carmack"--